Relative Effectiveness of 75Se and 125I as Labels for Rabbit Anticanine Urokinase - Vigorito, T.; Celander, D. R.; Celander, E. (Nuklearmedizin - NuclearMedicine, 1968)
75Se-labelled antiurokinase was isolated from the sera of rabbits which had received a series of canine urokinase injections followed, approximately 10 days before harvesting of the antibody fraction, by a single injection of 75Se as sodium selenite. An antibody fraction was also isolated from the sera of rabbits treated identically except for the omission of the canine urokinase from the injection series. Specific activity of the γ-globulin fraction of animals actively forming antiurokinase was considerably higher than that of the nonantiurokinase γ-globulin. When injected into mongrel pups, the radioactivity of the γ-globulin fraction containing antiurokinase was found predominantly in the kidney with the cortex of the organ possessing from 5 to 6 times as much activity per gram as kidney medulla. The radioactive antibodies from control animals appeared to be distributed among the various tissues examined in a random fashion with the activity of kidney cortex and kidney medulla being approximately equal. It is concluded that the kidney cortex constitutes a major site of storage, and possibly formation, of urokinase.Iodination of comparable rabbit γ-globulin fractions with 125I resulted in complete loss of specificity and in their failure to bind to tissues. The exact mode of incorporation of 75Se into the proteins of animals to which it is supplied as the inorganic selenite has not been elucidated. However, this radioactive tag does find its way into proteins where it remains firmly bound throughout the procedures involved in antibody purification and upon being injected into a recipient animal.